2005
DOI: 10.1590/s1519-69842005000400017
|View full text |Cite
|
Sign up to set email alerts
|

Limnological and ecotoxicological studies in the cascade of reservoirs in the Tietê river (São Paulo, Brazil)

Abstract: An evaluation was made of the quality of samples of water and sediment collected from a series of reservoirs in the Tietê River (SP), based on limnological and ecotoxicological analyses. The samples were collected during two periods (Feb and Jul 2000) from 15 sampling stations. Acute toxicity bioassays were performed using the test organism Daphnia similis, while chronic bioassays were carried out with Ceriodaphnia dubia and Danio rerio larvae. The water samples were analyzed for total nutrients, total suspen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
17

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 9 publications
2
27
1
17
Order By: Relevance
“…At Murum Reservoir, the concentration of DO reduced to 0 mg/L as it went deeper indicating anoxia state as a result of intensive decomposition of organic matter and submerged vegetation leading to depletion of oxygen. This result is similar to that reported in Barra Bonita Reservoir in Brazil (Rodgher et al 2005) and Bakun Reservoir in Malaysia (Nyanti et al 2012). Figure 3 shows the profile of DO concentrations at all stations.…”
Section: Temperaturesupporting
confidence: 91%
See 1 more Smart Citation
“…At Murum Reservoir, the concentration of DO reduced to 0 mg/L as it went deeper indicating anoxia state as a result of intensive decomposition of organic matter and submerged vegetation leading to depletion of oxygen. This result is similar to that reported in Barra Bonita Reservoir in Brazil (Rodgher et al 2005) and Bakun Reservoir in Malaysia (Nyanti et al 2012). Figure 3 shows the profile of DO concentrations at all stations.…”
Section: Temperaturesupporting
confidence: 91%
“…Temperature is a good indicator to determine thermocline (Dodson et al 2007), in the early stage of this study, thermocline occurrence was observed at 4 to 8 m depths. Table 2 shows the water temperature The dissolved oxygen concentration is a crucial environmental parameter in the dynamics and characterisation of aquatic ecosystems (Rodgher et al 2005). Figure 3 shows the profiles of dissolved oxygen at all stations.…”
Section: Temperaturementioning
confidence: 99%
“…In another study concerning spatial variation in a cascade system of six reservoirs located along the Tietê River (São Paulo State, Brazil), Rodgher et al (2005) and Smith et al (2014) observed that TN and TP showed the same patterns of variation in water and sediment, as suggested by the CRCC (Barbosa et al 1999). The patterns were similar to those observed in the present study.…”
Section: Resultsmentioning
confidence: 87%
“…The tested formulations were based on previous studies regarding the formation of natural sediments from 14 locations in the Tietê River system in four different periods (RODGHER et al, 2005). Tietê River is an important aquatic system impacted by a range of anthropogenic influences, and it is used for different purposes such as power generation, public water supply, and navigation.…”
Section: Formulationsmentioning
confidence: 99%